PENGEMBANGAN POTENSI DIRI DAN PENGEMBANGAN KARIR - ishak Arep (Media Riset Bisnis & Manajemen, 2003)
Each the manager of good for the administration authorityor private or firm, it is of course to desire the employees of firm always to obtain progress in servicing sector. Ideally, they are (the managers) in order to hope if the employees has pension, they are occupy a territory more high of possition than possifion before them to pension. Itmeans that, the employees must be try out more high of position than before them to take pension. Therefore, from the begin- ning every employees always bulding, teaching and training in order to the career can be expand with perfectfully and to could became a pioneer for the others employees or workers, moreover to try out can became samples or figure for superior or chairman to survival of firm or administration where they occupy an office.